Coaching to enhance the brand heritage of a Food and Beverages MSME in Kuala Lumpur, Malaysia - Efendi Efendi; Christianus Yudi Prasetyo; Florentine Vania; Isaiah Chesed; Fransisca Elvanty Kurniawan; Naila Nabilla Syafitri Komara; Francois Nathanael Salim (Journal of Community Service and Empowerment, 2025)
Conducting business after the Covid-19 outbreak is a challenging task for micro, small, and medium enterprises (MSMEs). They need to regain the customers lost during the pandemic.  This community service program aimed to assists a F&B MSMEs in Malaysia to increase its business performance. The team of community service from Faculty of Economics and Business, Atma Jaya Catholic University of Indonesia which consists of two lecturers and five students embark on a coaching session in Kuala Lumpur, Malaysia. The coaching session was conducted while the coachee was conducting his business in a food festival in Kuala Lumpur. There are four problems identified, which are human power, business information, business heritage, and social media promotion. The solutions offered to the coachee are creating more informative social media ads to recruit employees, put the business information in the container of the foods sold, and highlighting the heritage of the brand of Apam Balik & Kopi. Lastly, we suggest the coachee to conduct conditional discounts in social media.